KETAHANAN PANGAN RUMAH TANGGA PETANI SEKITAR TAHURA WAN ABDUL RACHMAN (WAR) DI DESA KEBAGUSAN KECAMATAN GEDONG TATAAN - Nanda Nur Rohmah; Zainal Abidin; Ktut Murniati (Lampung University, 2019)
The research goals were to determine the level of food security, farmers’ household dependences on Tahura WAR, know the relationship between income and household expenditure and the level of energy consumption. This research was conducted in Kebagusan Village, Gedong Tataan Subdistrict with respondents of 76 farmers around the Tahura WAR, which utilized the tahura and joined farmer groups. Data were analyzed quantitatively and statistically, i.e. the first goal with cross-classification between the share of food expenditure and household energy consumption level, the second by measuring the value of income contribution from Tahura WAR and other sources toward total income, and the third with the Pearson Product Moment correlation. The results showed that farmer households who achieved the level of food security as withstand was 17.11%, as vulnerable was 26.32%, as less was 34.21%, and food insecurity was 22.37%. Farmer households around Tahura WAR have a dependency on Tahura WAR which is indicated by the amount of income contribution from Tahura was 62.51%. Income has a negative relationship with food expenditure, but a positive relationship to nonfood expenditure. The income does not have a significant relationship with the level of energy consumption. Key words: Dependence, Food security, Tahura WAR